Enhancing Online Learning: Design Principles for More Effective Educational Web Forums - Watson, Shalini; Richards, C. (International Association of Technology, Education and Development (IATED), 2011)
Online educational web forums are increasingly being used in tertiary education settings to either supplement or replace face-to-face teacher-learner interactions. However, much use of such forums tends to be ad-hoc and ineffective which invariably results in dismal learner participation levels. This paper will report on a particular research inquiry into the design principles of a more effective and strategic use of educational web forums within particular coursework contexts and in relation to a range of possible learning outcomes. It will therefore focus especially on the design challenge of two issues in particular. The first is the inherent communication limitations as well as opportunities represented by typical web forum functions. A second related issue lies in the challenge of reconciling in practice both participant-related factors and course-design related factors. Participant-related factors include personal profiles, prior learning experiences and educational perspectives. Conversely course-design related factors include the quality and quantity of assessment items, the communication of unit requirements and the underlying approach to learning and facilitation of the unit. In this way the paper will explore how a more strategic negotiation of the intrinsic and extrinsic factors of coursework participation can be a design basis for more effective online learning and active learner participation.